Relative Contribution of Haptic Technology to Assessment and Training in Implantology. (20th February 2014) - Joseph, David; Jehl, Jean-Philippe; Maureira, Pablo; Perrenot, Cyril; Miller, Neal; Bravetti, Pierre; Ambrosini, Pascal; Tran, Nguyen
Abstract : Background . The teaching of implant surgery, as in other medical disciplines, is currently undergoing a particular evolution. Aim of the Study . To assess the usefulness of haptic device, a simulator for learning and training to accomplish basic acts in implant surgery. Materials and Methods . A total of 60 people including 40 third-year dental students without knowledge in implantology (divided into 2 groups: 20 beginners and 20 experiencing a simulator training course) and 20 experienced practitioners (experience in implantology >15 implants) participated in this study. A basic exercise drill was proposed to the three groups to assess their gestural abilities. Results . The results of the group training with the simulator tended to be significantly close to those of the experienced operators. Conclusion . Haptic simulator brings a real benefit in training for implant surgery. Long-term benefit and more complex exercises should be evaluated.